1984
DOI: 10.2131/jts.9.131
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of adrenergic and serotonergic nervous mechanisms in allethrin-induced tremors in mice.

Abstract: Oral or intravenous administration of allethrin, a synthetic derivative of the pirethrin-based insecticides, produces neurotoxic symptoms consisting of mild salivation, hyperexcitability, tremors and convulsions which result in death. Intracerebroventricular injection of allethrin to mouse at about one-nineth the dose of intravenous administration, produced qualitatively identical but less prominent symptoms, indicating that at least some of the symptoms may be originated in the central nervous system. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The behavioral observations conducted 20-30 years ago (e.g. [175,98,127]) support this assumption. The T(Type I)/CS (Type II)/TS(Type I/II) classification scheme established in these studies is still useful for systematic comparison of acute poisoning syndromes between older and "modern" pyrethroids and across different insecticide classes.…”
Section: Ratmentioning
confidence: 85%
See 2 more Smart Citations
“…The behavioral observations conducted 20-30 years ago (e.g. [175,98,127]) support this assumption. The T(Type I)/CS (Type II)/TS(Type I/II) classification scheme established in these studies is still useful for systematic comparison of acute poisoning syndromes between older and "modern" pyrethroids and across different insecticide classes.…”
Section: Ratmentioning
confidence: 85%
“…administration of pyrethroids, the time course for the development of poisoning signs in insects and mammals is comparable. A latency of seconds to minutes from dosing to the onset of poisoning signs is seen in both cases [98,62,127,13,139,39]. In rodents, the onset of poisoning signs correlates with the accumulation of an internal dose in nervous system tissue [180,70,66,74,146].…”
Section: Comparative Toxicity Between Target and Non-target Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports from studies using similar dosing protocols in rats demonstrated maximal decreases in figure-eight maze activity at 1–4 hr postdosing (Crofton et al 1995; Crofton and Reiter 1984, 1988; McDaniel and Moser 1993; Wolansky et al 2006). In addition, allethrin, S -bioallethrin, permethrin, fenvalerate, delta-methrin, and cypermethrin evoke alterations in motor-related end points in small rodents evident as early as 0.5–1.5 hr after systemic exposure (De Souza Spinosa et al 1999; Hoy et al 2000; McDaniel and Moser 1993; Nishimura et al 1984; Wolansky et al 2006). Likewise, the extended effect on activity through 8 hr is consistent with the prolonged syndromes evoked by resmethrin and bifenthrin (Crofton and Reiter 1984; Holton et al 1997; Soderlund et al 2002; White et al 1976; Wolansky et al 2006, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism of action for all pyrethroids is the prolongation of the open state of neuronal voltage-dependent sodium channels (Narahashi 1971; Vijverberg and van den Bercken 1990). This action results in altered neuronal excitability characterized by in vitro and in vivo changes in neuronal firing rates (e.g., repetitive firing or depolarizing block of the neuron) (Narahashi 2000) that are associated with two high-dose neurologic syndromes, T syndrome and the CS syndrome (Aldridge 1990; Barnes and Verschoyle 1974; Lawrence and Casida 1982; Ray and Forshaw 2000; Ray and Fry 2006; Verschoyle and Aldridge 1980), and dose-dependent changes in motor and sensory behaviors at lower doses (Chanh et al 1984; Crofton and Reiter 1984 1988; Hornychova et al 1995; McDaniel and Moser 1993; Nishimura et al 1984; Wolansky et al 2006; Wolansky and Harrill 2008). …”
mentioning
confidence: 99%